Inhibitory Effects of Oyster Shell on the Spathe “Greenback” of Anthurium andraeanum Lind. - Xia Chun-hua; Chen Yi-wei; Chen Jian-hua (E3S Web of Conferences, 2019)
Anthurium andraeanum Lind. is an important tropical flower. However, the spathe of A. andraeanum develops a ”greenback” under low-light conditions. This study aimed to evaluate the use of oyster shell supplementation as a cultivation technique for inhibiting the spathe “greenback” of A. andraeanum under low-light conditions. Appropriate calcium from micro-dissolution of oyster shell can improve the activity of phenylalanine ammonia lyase (PAL) which is positively correlated with the anthocyanin content. Using regression models and response surface methodology (RSM), the relationships between oyster shell fragments and the anthocyanin content were determined. The results showed that the solubility of oyster shells increased with the increase in fragment weight, C, and time, T at pH 5.9. In oyster shell substrate, cultivation of A. andraeanum under low-light conditions (less than 220 μmol·m−2·s−1) at pH 5.9, regression analysis showed that the PAL activity in pedicels of A. andraeanum first increased and then decreased with the increase in oyster shell fragment weight C, and the 286 mg oyster shell fragments greatly increased the PAL activity of A. andraeanum pedicels within 8 weeks (w). The 286 mg oyster shell fragments significantly increased the anthocyanin content in A. andraeanum spathes under weak-light conditions within 8 h, and the soluble sugar content reached the maximum value at 15 weeks as well, together with the pedicel diameter, soluble sugar and water content, thus inhibiting the spathe “greenback” of A. andraeanum.